New Attorney Swearing In Ceremony Held in State Building Auditorium - Watkins, Howard::::::::: (1986)
Appellate Court's Chief Deputy Clerk Vickie Hernandez and Justices Frank Hoover (by assignment), Charles Hamlin, Wickson Woolpert, Donald Franson, Presiding Justice George Brown, Pauline Davis Hanson, Robert Martin and Hollis Best Seated at table on stage